Fractured frontiers : the exile writing of Nazi Germany and Francoist Spain - Jato, Mónica; Klapper, John (Camden House, 2020)
"A comparative study of "inner" and "territorial" forms of literary exile under Nazism and Francoism, proposing an integrative model of exile that emphasizes common approaches and themes rather than division"--